Soybean Seed Quality: An Empirical Analysis on Clayey Soils in Arkansas. Issue 1 (12th June 2015) - Popp, M.; Rupe, J.; Rothrock, C.; Ross, J.; Dixon, B.; Steger, A.; Lutes, J.
Abstract : Soybean [ Glycine max (L.) Merr.] seed quality is an important factor for seeding rate recommendations. Which seed quality measure to use for seeding rate recommendations and how seed treatment and planting date affect returns are assessed within. Results suggest that adding seed vigor information to seed labels would be beneficial in providing seeding rate recommendations. Seed treatment is profitable and more so at lower seeding rates. Seed survival impacts yields, but seed quality effects do not affect yield potential post–plant establishment. Planting season is an important determinant of seed survival and yield potential.